Analysis of Sharia Marketing Mix and Service Quality on Consumer Purchasing Decisions at Deliwafa Store Gresik - Muhammad Syadam Wiro Aji; Malik, Ahmad Dahlan; Muhammad Asyhad (Sustainability and Social Impact, 2024)
This research includes the sharia marketing mix in the form of promotion, product quality, price and service quality. These four discussion variables have an important role in the sustainability of customer decisions. This study aims to determine what factors make decisions in consumer purchases. The research method uses quantitative research methods in which the data obtained is then processed using PLS (Partial Lest Square) analysis, in this study describing the results of detailed analysis through distributing questionnaires to 109 respondents where the criteria for filling out questionnaires include consumers who shop at the Deliwafa Store Gresik branch. This study also looks at the relationship and model and determines the dominant variable using software data processing using SmartPLS version 4. From the results of this analysis, it shows that the Promotion (X1) and Price (X3) variables have a significant influence on Purchasing Decisions (Y) Deliwafa Gresik Branch. While the Product (X2) and Service Quality (X4) variables are opposite